(untitled) (Orfeu, 2020)
Although less discussed in the field of historical musicology in Brazil than archives, library collections also contain sources of interest to the study of music. This article seeks to understand the constitution of the rare works section of the library of Grêmio Literário e Recreativo Português [Portuguese Literary and Recreational Society] of Pará, observing signs that suggest or rule out the hypothesis that the items in the section and, more specifically, those of musical interest – a book for processions, theory books and bound librettos, dating from the 17th and 18th centuries – have taken local uses at the time of their production. For this purpose, a fieldwork was carried out in Pará and Lisbon, using the theoretical framework of Cataldo and Loureiro, Mouren and Candau. The results point to the probable acquisition of bibliographic items in the 19th century, which, although they do not seem to be related to local musical practices, their selection reflects the intentional affirmation of a Luso-Amazonian identity.